Plan de rehabilitación ecológica, manejo y conservación de los humedales de la quebrada El Estero, San Ramón, Alajuela - Rodríguez-Arias, Cindy (Instituto Tecnológico de Costa Rica, 2017)
The wetlands of the high watershed of the Estero creek are formed by this stream and a tributary, a swamp and two reservoirs that are the last remnants of an ancient lake that existed in the San Ramon area and are considered a conservation priority due to their representativeness and location that makes them unique in its kind. However, in recent decades they have suffered a degradation processes that not only threaten the conservation of ecosystems, but the security of the human population. Therefore, the objective of this investigation was to formulate a proposal for a rehabilitation, management and conservation plan for these wetlands in favor of the rehabilitation of ecosystem services such as biodiversity conservation, flood mitigation, recreation, environmental education and scientific research. To begin with, an assessment of the current state of the wetlands was carried out, including the study of the physico-chemical and microbiological water quality, conservation status of birds and aquatic plants communities as bioindicators and the identification of ecosystem services provided by the wetlands and the threats and impacts of human activities on them. Based on this assessment, an ecological rehabilitation plan was proposed. It was determined that these wetlands are being degraded due to rapid urbanization in its upper watershed, which has caused water pollution mainly by domestic sources, spread of invasive species, loss of habitat for aquatic species, stuffing in some areas of the swamp, invasion of protection zones, eutrophication and silting of reservoirs and decrease in their ability to mitigate floodings in the city of San Ramon. Therefore, due to the state of degradation and the lack of a reference ecosystem or ecological information prior to degradation, an ecological rehabilitation plan was proposed, aimed at solving the problems identified and to the recovery of ecosystem services. The plan consists of six programs based on the following elements to intervene: hydroperiod and hydrological regime, water quality, soil and sediments, invasive exotic species and domestic predators and native flora and fauna. In addition, a program that allows the participation of civil society in the different stages of the project was included. Finally, strategies for monitoring and viii management of wetlands once they are rehabilitated are also included. As a result of this investigation and because of the social and environmental importance of these wetlands, the Western Headquarters of the University of Costa Rica created the research program for the recovery and sustainability of the upper watershed of the Estero creek, composed of 11 research and social action projects in different disciplines. This program has coordinated with other institutions, civic groups and local companies, which have allowed that some of the actions included in this proposal are already underway.
Tesis (Doctorado en Ciencias Naturales para el Desarrollo con énfasis en Gestión de Recursos Naturales) Instituto Tecnológico de Costa Rica. Universidad Nacional de Costa Rica. Universidad Estatal a Distancia, Doctorado en Ciencias Naturales para el Desarrollo, 2017.
Keywords: Educación ambiental; Flora; Fauna; Conservación; Biodiversidad; Calidad del agua; Mitigación de desastres; Inundación; Research Subject Categories::NATURAL SCIENCES